La libertà umana in Blaise Pascal alla luce delle fonti prossime e remote - Soliani, Gian Pietro (Gregorianum, 2025)
The article is aimed to examine the most relevant sources, remote and proximate, of Pascal's account of human freedom. Pascal never devoted a specific consideration to this topic. However, his theological works contain several remarks on divine grace, and its action on human free will. Even if Pascal does not seem to support a particular philosophical perspective, in the Writings on Grace, he employs the scholastic concept of freedom of indifference, briefly elucidating it and manifesting the influence of both Descartes' Meditationes and Jansenius's Augustinus. The article analyses Jansenius' voluntaristic doctrine on freedom built as a syncretistic intersection of theses inspired by Augustine, Thomas Aquinas, and Duns Scotus. Pascal never quotes those theses. Furthermore, in the eighteenth letter of his Provincial Letters, he defends the so called "Augustine's disciples" through the authority of the Dominican Diego Alvarez, who supports an antivoluntaristic theory of freedom. By investigating a complex and braided set of remote and proximate sources, the article provides new insights on Pascal's theological background and tries to show an evolution in Pascal's thought from the Writings on Grace up to the Thoughts and Provincial Letters.